The Relationship Between Spirituality and Depression Levels in the Elderly at Graha Senior Resident Karya Kasih, Medan - Sinurat , Samfriati; Ginting , Friska Sri Handayani; Febiola, Sherina (Journal of Nursing Science Update (JNSU), 2024)
Elderly individuals frequently experience declines in biological, psychological, social, and spiritual functioning, particularly those residing in orphanages who encounter considerable psychological challenges such as depression. The objective of this study is to investigate the relationship between spirituality and depression levels within the elderly population at Graha Residen Senior Karya Kasih, Kota Medan. This research employed a correlational design utilizing a cross-sectional approach. The sampling technique used was purposive sampling, with participants selected based on the criteria of being 60 or older and possessing practical communication abilities. A total of 41 respondents participated in the study. The instruments employed included the Daily Spirituality Experience Scale (DSES) and the Geriatric Depression Scale (GDS). The study found that 40 participants (97.6%) reported positive spiritual experiences, while nearly half (20 individuals or 48.8%) showed symptoms of depression. Statistical analysis revealed a significant negative relationship between spirituality and depression in older adults, with a Spearman rank p-value of 0.007 and a correlation coefficient of -0.415. In conclusion, higher spirituality is linked to lower depression levels, although depressive symptoms can still be present. The researcher recommends enhancing spirituality and suggests reminiscence therapy as a possible intervention for depression in older adults.